Improving analgesia in fractured neck of femur with a standardised fascia iliaca block protocol. Issue 1 (6th May 2016) - Watson, Paul; Rugonfalvi-Kiss, Szabolcs
Abstract : Fractured neck of femur (NOF) causes significant morbidity and pain for patients; adequate analgesia is an essential component of patient centred care. Patients experiencing greater pain during treatment for fractured NOF are slower to mobilise and have poorer health-related quality of life. NICE guidance suggests considering adding nerve blocks if paracetamol and opioids do not provide sufficient preoperative pain relief. We set out to audit pain levels in this group of patients in a small District General Hospital and to develop a protocol to improve analgesia provision if required. We identified that patients waiting a long time for fixation of fractured NOF could benefit from safe, effective analgesia by way of fascia iliaca compartment block (FICB). We drew up a protocol and held training sessions bringing about a culture change to provide an excellent standard of analgesia for these patients. Most patients reported much better levels of analgesia post-block and junior doctors felt more empowered. Further developments considered are training of senior ED nurses to administer FICB (in keeping with the AAGBI position statement) and a fascia iliaca catheter placement service.